2022
DOI: 10.1039/d2ta07316a
|View full text |Cite
|
Sign up to set email alerts
|

An artificially tailored functional layer on Li-rich layer cathodes enables a stable high-temperature interphase for Li-ion batteries

Abstract: The unstable electrode-electrolyte interphase, poor rate capability, and severe lattice oxygen release of Li-rich layer oxides (LRNCM) severely limit their commercial application. Herein, an ultrathin Li2SiO3 (LSO) protective layer with...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 70 publications
0
6
0
Order By: Relevance
“…Dissolved TMs react with F-ions to generate a TMF 2 layer, continuously depositing onto the surface of the active site and forming an uneven CEI layer. This uneven layer significantly hampers ion transport, thereby diminishing battery performance . The dissolution of TMs, a pivotal factor contributing to the deterioration of positive electrode materials, was investigated using ICP-OES .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Dissolved TMs react with F-ions to generate a TMF 2 layer, continuously depositing onto the surface of the active site and forming an uneven CEI layer. This uneven layer significantly hampers ion transport, thereby diminishing battery performance . The dissolution of TMs, a pivotal factor contributing to the deterioration of positive electrode materials, was investigated using ICP-OES .…”
Section: Resultsmentioning
confidence: 99%
“…This uneven layer significantly hampers ion transport, thereby diminishing battery performance. 52 The dissolution of TMs, a pivotal factor contributing to the deterioration of positive electrode materials, was investigated using ICP-OES. 53 After 100 cycles at elevated temperatures via the RF method, the contents of Ni, Co, and Mn on lithium tablets were 0.0004, 0.0021, and 0.1208 mg/L, respectively, which were lower than 0.0005, 0.0035, and 0.2122 mg/L through the NF method.…”
Section: Electrochemical Performances Of Lnmc622||limentioning
confidence: 99%
“…[1][2][3][4] The choice of electrode materials is crucial to the battery's overall performance. [5][6][7] Therefore, people have developed various electrode materials, such as carbon-based materials, [8][9][10] silicon-based materials, 11,12 titaniumbased materials, 2,13 vanadium-based materials, [14][15][16][17][18] and so forth. [19][20][21][22] Among a variety of electrode materials, vanadiumbased sulfides have attracted much attention attributed to their high capacity and abundant valence states.…”
Section: Introductionmentioning
confidence: 99%
“…For example, it has been reported that the retention capacity of current commercial lithium-ion batteries (LIBs) at −40 °C is only 12% of the room temperature value . On the contrary, if the electrochemical reactions of LIBs are exposed to a high-temperature environment for a long time, it will also exacerbate the metal dissolution and lattice oxygen release in the electrode material, accompanied by the materials’ irreversible structural transformation . Fewer studies have been able to incorporate temperature variations into the operando characterization apparatus.…”
mentioning
confidence: 99%